Using prism adaptation to alleviate perception of unilateral tinnitus: A case study. (December 2022) - Bonnet, Clémence; Poulin-Charronnat, Bénédicte; Rossetti, Yves; Perrot, Xavier; Michel-Colent, Carine
Abstract: Tinnitus is described as an uncomfortable sound or noise heard by an individual in the absence of an external sound source. Treating this phantom perception remains difficult even if drug and nondrug therapies are used to alleviate symptoms. The present case study aimed to investigate whether prism adaptation could induce beneficial aftereffects in a tinnitus sufferer. A 75-year-old man, R. B., with chronic unilateral tinnitus in the left ear reported a self-estimation of parameters of his tinnitus—discomfort, pitch and loudness—and performed a manual line-bisection task to study the consequences of lateralized auditory disorder on spatial representation. Aftereffects of prism adaptation were assessed using a sensorimotor open-loop pointing task. In parallel, a control group completed the line-bisection task and the open-loop pointing task before and after lens exposure, under the same experimental condition as those of R. B. Throughout the pretests, the patient assessed his tinnitus at a constant medium pitch (around 3000 Hz), and he was biased toward the affected ear in both the sensorimotor task and the estimation of the subjective center in the manual line-bisection task. Although both optical deviations were effective, an exposure to prism adaptation to a rightward optical deviation (i.e., toward the unaffected ear) produced stronger aftereffects. In posttests, the tinnitus pitch decreased to 50 Hz and the subjective center was shifted toward the right side (i.e., unaffected ear side). Furthermore, the line-bisection task seemed to reflect the changes in the tinnitus perception, and spatial representation could be a new tool to assess tinnitus indirectly. Our findings suggest that prism adaptation may have benefits on unilateral tinnitus and open a new avenue for its treatment.